2020
DOI: 10.12688/f1000research.24086.2
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: IgG multiple myeloma and chronic myeloid leukemia in a single patient

Abstract: A 58-year-old man presented with recurrence of chronic myeloid leukemia (CML) after complete molecular remission in the setting of non-compliance with imatinib. He was restarted on imatinib and was also noted to have IgG kappa monoclonal gammopathy of undetermined significance (MGUS). The patient re-achieved molecular remission after resumption of imatinib, but his MGUS progressed to smoldering myeloma and he was eventually diagnosed with multiple myeloma (MM) and initiated on treatment for MM with thalidomide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…None of our patients was diagnosed with active MM. In the literature, the coexistence of MM and CML in a single patient has rarely been reported, with only several dozens reported so far [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Most reported cases included patients in whom the diagnosis of MM followed a prolonged treatment period with imatinib for CML, leading to the hypothesis of a possible link between this treatment and the development of MM [5][6][7][8][9][10][11][12].…”
Section: And CMLmentioning
confidence: 99%
See 2 more Smart Citations
“…None of our patients was diagnosed with active MM. In the literature, the coexistence of MM and CML in a single patient has rarely been reported, with only several dozens reported so far [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Most reported cases included patients in whom the diagnosis of MM followed a prolonged treatment period with imatinib for CML, leading to the hypothesis of a possible link between this treatment and the development of MM [5][6][7][8][9][10][11][12].…”
Section: And CMLmentioning
confidence: 99%
“…In the literature, the coexistence of MM and CML in a single patient has rarely been reported, with only several dozens reported so far [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Most reported cases included patients in whom the diagnosis of MM followed a prolonged treatment period with imatinib for CML, leading to the hypothesis of a possible link between this treatment and the development of MM [5][6][7][8][9][10][11][12]. Carulli et al [38] found imatinib treatment for CML to induce a plasma cell phenotype with the same characteristics as that in monoclonal gammopathies according to multiparametric flow cytometry from bone marrow aspirates of 30 CML patients treated with imatinib.…”
Section: And CMLmentioning
confidence: 99%
See 1 more Smart Citation